Research in foster care: The methodological issues and how the issues are addressed - Chan, Cheong Chong (American-Eurasian Network for Scientific Information (AENSI Publisher), 2013)
Foster care studies are popular in child welfare research and have been widely conducted in the West.However, there is no common understanding on the best practices in designing and conducting a foster care research.This paper discusses the common methodological issues found in the current foster care literature.A brief review was conducted on selected foster care articles and research reports.The review shows that there are seven common methodological issues in foster care studies namely, cross-sectional design, comparison group, adult centric, sample size, standardized instrument, male caregivers and the dilemma of quantitative vs. qualitative. In line with this, how the issues are addressed by researchers is also discussed.